Multiplexer Performance Testing For IoT-Based Air Quality Monitoring System: Multiplexer Performance Testing For IoT-Based Air Quality Monitoring System - Bakti Dwi Waluyo; Harvei Desmon Hutahaean; Agus Junaidi (Jurnal Mantik, 2020)
Technology-based on the Internet of Things (IoT) which is integrated with the NodeMCU ESP8266 device has produced intelligent equipment.The smart equipment is even able to display data in real-time through computer devices and smartphones while connected to the internet.However, NodeMCU ESP8266 has limitations on analog input channels, so sensors with analog output cannot be connected more than one.therefore, the multiplexer in the form of IC 4051 is used to add analog channels in NodeMCU ESP8266.IC 4051 has eight analog channels which are controlled by selector pins. Sensors connected to IC 4051 are temperature (LM35), humidity (HIH-4030), gas (MQ-2 and MQ-135).NodeMCU ESP8266 receives values ??from sensor readings and sends to the Firebase database via internet connection.The firebase database can be monitored via a smartphone by making its application on the MIT App Inventor.This experiment has succeeded in acquiring data from the four sensors using a multiplexer, then the data can be viewed via a smartphone.